Review of the genus Microphilypnus Myers, 1927 (Teleostei: Gobioidei: Eleotridae) from the lower Amazon basin, with description of one new species - Caires, Rodrigo A.; de Figueiredo, José Lima (Zootaxa, 2011)
Microphilypnus Myers, 1927 is a genus with three nominal species (M. amazonicus and M. macrostoma from the lower Amazon basin, and M. ternetzi from Orinoco), and is among the most poorly studied groups of Neotropical fishes. In this paper, M. ternetzi and M. macrostoma are redescribed and validated and M. amazonicus is regarded as synonym of M. ternetzi. Also, a new species, M. acangaquara, is described from the lower Amazon.